Acoustic emission analysis of characteristics of healing products in steam-cured cementitious materials with mineral additives. (20th March 2019) - Jiang, Zhengwu; Yuan, Zhengcheng; Li, Wenting
Highlights: The self-healing capability of steam-cured mortar was investigated for the first time. AE signals can distinguish damage stage between healing products and host matrix. The amount and energy of healing products can be qualitatively assessed by AE signals. Abstract: The objective of this work is to investigate the self-healing performances of steam-cured mortars with mineral additives (e.g., calcium-based materials, chemical expansive agents and crystalline components). The self-healing capabilities of crack was evaluated by transport tests and acoustic emission (AE) analysis for cracked mortars. The two representative AE parameters, i.e., amplitude and energy, were used to reveal the characteristics of healing products. The results showed that the improvement of transport properties of cracked steam-cured mortars were more effective compared to standard-cured mortars. The healing efficiency can be further improved by utilizing mineral additives. The differences of damage stage between healing products and host matrix can be distinguished by AE signals. Upon reloading of steam-cured mortar with mineral materials, the number of amplitude were much larger and the cumulative energy was much higher compared to other mortar. It indicated that the steam-cured mortar with mineral materials possessed larger amount and much higher energy healing products in the crack to some extent, which were well consistent with that of transport properties and microscopic observation.